Arabic Vocabulary Learning Strategies Based on Al-Af’al al-Yaumiyyah for Ulya Student at Ma’hadut Tholabah Islamic Boarding School - Tazkiyatun Nufus; Faliqul ISbah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This research was motivated by the low Arabic vocabulary mastery among students in the ulya class at the Ma'hadut Tholabah Babakan Tegal Islamic Boarding School, particularly in understanding and using vocabulary contextually in everyday communication. The book Al-Af'al al-Yaumiyyah, a learning resource containing vocabulary for daily activities, has not been optimally utilized in the learning process. This study aims to describe and analyze vocabulary learning strategies based on this book and evaluate their effectiveness in improving Arabic vocabulary mastery. This study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results showed that the learning strategies implemented included vocabulary presentation, repetition (drill), practice of usage in everyday communication, and assignments on memorization and sentence construction. The implementation of these strategies proved effective in improving students' vocabulary mastery, activeness, and learning motivation. Furthermore, a supportive language environment contributed to the success of the learning. Thus, vocabulary learning strategies based on the book Al-Af'al al-Yaumiyyah can be an effective, contextual, and applicable alternative in improving the Arabic language skills of students in Islamic boarding schools.